THE STATISTICAL NATURE OF ECONOMIC DATA - Mullabayev Baxtiyarjon Bulturbayevich; Ismoilov Abdulkholik (Journals Park Publishing, 2022)
This article provides insights and comments on the statistical nature of economic data.
Keywords: statistical analysis; event; correlation analysis